Menyingkap Representasi Perempuan Dan Simbol Agama Dalam Poster Film Horor Indonesia: Melampaui Stereotip - Pratiwi, Sekar; Fauziyyah, Ifa Bilqiis; Wahyudi, Luqman (Institut Seni Indoensia Surakarta, 2024)
The Indonesian religious-themed horror film industry, as exemplified by Kiblat, Siksa Neraka, and Sijjin, leverages religious symbols to evoke fear and tension, presenting a stark contrast between sacredness and horror. However, this approach has sparked public controversy, with many perceiving it as a desecration of religious sanctity, leading to protests and boycotts that underscore the tension between artistic expression and religious values in Indonesian society. Furthermore, the portrayal of women in these films' posters often reinforces patriarchal stereotypes by depicting them as victims or objects of violence, perpetuating narratives of female subordination and hindering progress toward gender equality. Through Stuart Hall's Representation Theory, this study analyzes the visual and ideological construction of religious symbols and female figures in Indonesian horror film posters, exploring their denotative and connotative meanings to understand the genre's role in shaping social discourse on religion and gender within Indonesia's cultural context.